Colchicine in patients with aortic stenosis undergoing transcatheter aortic valve replacement: a double-blind randomized trial - Christoph Ryffel; Jonas Lanz; Nicole Guntli; Daryoush Samim; Monika Fürholz; Stefan Stortecky; Daijiro Tomii; Dik Heg; Martina Boscolo Berto; Alan Arthur Peters; David Reineke; Tobias Reichlin; et al. (Nature Communications)
Abstract An inflammatory process may increase the risk of arrhythmias after transcatheter aortic valve replacement (TAVR). In this single-centre, double-blind, placebo-controlled, randomized trial we investigated the efficacy of colchicine to reduce a composite of new-onset atrial fibrillation or atrioventricular conduction disturbances requiring the implantation of a permanent pacemaker at 30 days after TAVR. Between September 21, 2021 and April 25, 2024, 120 patients with aortic stenosis undergoing TAVR (mean age 80.6 ± 5 years, 64% male) were randomly allocated to treatment with colchicine (n = 60) or placebo (n = 60). The trial was prematurely stopped due to a higher rate of stroke in the experimental group in a pre-specified interim analysis (5 [8.3%] versus 0 at maximum available follow-up, p = 0.022). In the intention-to-treat population, the primary endpoint occurred in 6 patients (10%) in the colchicine group and in 15 patients (25%) in the placebo group (risk-difference −15.0%, 95% CI −28.3 to −1.7, p = 0.031). The prespecified imaging endpoint, subclinical leaflet thrombosis, was detected in 13 of 48 patients (27%) in the colchicine group versus 26 of 48 patients (54%) in the placebo group (risk difference −27.1%. 95% CI −46.0% to −8.2%, p = 0.007). Here, we show that periprocedural treatment with colchicine may reduce the incidence of new-onset arrhythmias and subclinical leaflet thrombosis after TAVR. However, given the premature termination of the trial due to an unexpected increase in the stroke rate among patients treated with colchicine, confirmatory trials are warranted to corroborate the effect of anti-inflammatory treatment on the incidence of arrhythmias and subclinical leaflet thrombosis after TAVR. The trial was an investigator-initiated study supported by dedicated grants from the Bangerter-Rhyner Foundation and the Swiss Life Foundation. ClinicalTrials.gov Identifier: NCT04870424.